Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 91 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Connochaetes taurinus (Burchell, 1823)", "Country is Tanzania, United Republic of", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 91 records from 9 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004314-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences